Pengaruh unemployment rate terhadap tingkat depresi dan anxiety dengan unemployment benefit sebagai mediator - Primadanik, Maylinda; Simanjuntak, Robert Arthur (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study contributes to the growing the literature on the relationship between unemployment rate on depression and anxiety’s index. By adding the unemployment benefit variable as a mediating variable, this study aims to determine the direct effect, indirect effect and total effect of the relationship between the unemployment rate and depression and anxiety’s index. In addition, this study also analyzes the role of the unemployment benefit variable in mediating the relationship between the unemployment rate variable and depression and anxiety’s index. By using the path analysis method of panel data, this study shows (1) in Vietnam, the appreciation of the unemployment rate indirectly increases the level of depression and anxiety by including the unemployment benefit variable as a mediator and (2) in Japan, the appreciation of the unemployment rate can indirectly increase the level of depression and anxiety by including the variable unemployment benefits as a mediator. Overall, the variable of unemployment benefits in Vietnam and Japan mediates variables partially (partial mediation).